Development of an online report card system (ORCS) using clustering index technique / Siti Hasmah Ismail - Ismail, Siti Hasmah (2008)
The teachers at Sekolah Kebangsaan Seksyen 7, Shah Alam are using a report card system to key in examination data. But the system is stand alone system. The reports still need printed out for the parent's information. All students' examination result sare kept in difference file based on their class. In order for parents to monitor the children's academic progress, and their social development and also for the teachers to key in the student's data like examination results, assignments and tests mark and also about social behavior, the development of an online report card is necessary. Online Report Card System is a system to manage and monitor the student's academic performance and also their social behavior. The clustering index technique in data organization for the database has been implemented in the Online Report Card System, since it has been improved the storage and retrieval of data. This technique can give benefits in increasing performance of query to search for range of data. Thus, the effective use of online report card could possibly improve the way for report card management and the way for parent monitoring their child's.